Expanding Ethical Horizons: Rethinking the Ethics of De 德 and Guṇa in the Laozi 老子 and Bhagavad-Gītā - Pritam Saha (Religions)
This paper aims to engage in an ethical discussion of de in the Laozi and guṇa in the Bhagavad-Gītā to expand the horizon of our ethical understanding of Chinese and Indian philosophy. First, this paper will explore the different ethical levels of de and guṇa and discuss how these levels operate and are bound together. From an ethical perspective, this paper points out that de and guṇa can each be divided into two parts—higher de and lower de, and higher guṇa and lower guṇa. It will further explain the ethical significance of de and guṇa, arguing that they offer a unique contribution to developing our contemporary understanding of ethics. We will also seek to discover the interplay of de and/with the dao in the Laozi and that among the three guṇas in the Gītā from the perspective of human behaviors. In the conclusion, we will provide a comparative discussion of our findings on the ethics of de and guṇa in the Laozi and the Gītā. These findings suggest that de and guṇa promote a shared philosophical outlook within their respective traditions and thereby make a contribution to post-comparative ethical approaches.